'Everyone Has Monsters Within': Neoliberal Release of Monstrous Desire in Stuart Gordon's Re-Animator (1985) and From Beyond (1986). Issue 2 (July 2022) - Morgart, James
Abstract : This article argues that filmmaker Stuart Gordon uses the Gothic to critique neoliberal desires that proliferated during the 1980s and continue to exist today. Gothic tropes, particularly monstrosity, coincide with the political in a number of Gothic works by filmmakers such as Tobe Hooper, Larry Cohen, John Carpenter and David Cronenberg. Examining a number of these works reveals that monstrosity is designated to characters who privilege individual desires over the community; however, by closely reading Gordon's Re-Animator (1985) and From Beyond (1986) alongside these films, I argue that Gordon's films offer the more chilling recognition for audiences that neoliberalism's real power is in its ability to adapt itself to appeal to and ultimately exploit our desires no matter how benevolent we believe them to be.